Influence of Technological Trends in the Automobile Industry on the Information Seeking Behaviour of Mechanics in Ghana - Boatemaa Asare, Comfort Akosua; Larteley Adu, Theresa; Akwei Mills, Nathaniel Leslie (Ghana Library Journal, 2024)
The purpose of the study was to determine how information and communications technologies influence the information seeking behaviour of artisans in the automobile industry in Ghana. Questionnaires made up of open- and closed-ended questions were used to collect data from 206 artisans in the automobile industry from the Ga North, Ga East as well as the Madina municipalities within the Greater Accra Region, Ghana, which have high population of mechanics. The low educational background of most mechanics in the information seeking and application of information to problem solving, affected their operations. Most mechanics had on the-job-training instead of formal training, which informed their poor ICT skills relevant in their field of work. The high cost of relevant technology tools also demotivated most mechanics from acquiring them for their work. The use of ICT tools plays a major role in the activities of artisans in the current state of the automobile industry worldwide, and there is the need for governments to collaborate ith some state agencies and non-governmental organizations in ensuring that these artisans are given the needed support in ICT training to make them more relevant in the discharge of their duties.